Semantika glagola čulne percepcije u staroslovenskom jeziku - Grković-Mejdžor, Jasmina (Slavistična revija, 2011)
This article deals with semantics of the Old Church Slavonic perception verbs oštutiti, čuti, viděti, ględati, z´rěti, slyšati, slušati. The research, basedon the corpus of the Codex Marianus, encompasses the analysis of their syntactic-semantic features and tne conditions which enable their metaphorization into the domain of "mental perception". In the conclusion the author points out the semantic features on which the mapping from the domain of sensory perception into the cognitive domain is based, as well as the way in which Old Churc Slavonic linguistic structures represent the cognitive dynamics of perception and cognition.
Keywords: Codex Marianus; čutno zaznavanje; glagol; historical semantics; manuscripts; Marijanski evangelij; metaforika; Old Church Slavonic language; perception verbs; rokopisi; semantics; semantika; stara cerkvena slovanščina; verb